Pesan Moral Komunikasi Orang Tua Dan Anak Dalam Alquran: Analisis Metode Tafsir Tematik - Tsauri, M. Najib (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
This paper discusses the interpretation of verses of parent and child communication from the Qur'an. The purpose of this discussion is to explore the moral message of parent and child communication that is the object of discussion. The object of this research is the Prophet Ibrahim and his son, Luqmān and his son, Prophet Ya‘qūb and his son, and Prophet Nūḥ and his son. The importance of this discussion is to find moral values ​​or messages in the stories in the Qur'an which will later become ibrāh or lessons for Muslims. To get in-depth results, this study uses a thematic method. As the name implies, this method is an attempt to understand the verses of the Qur'an by seriously studying the related verses.